The Interplay of Organizational Culture and Governance in Enhancing Sustainability Performance - Abdulrahim, Mohamed Omar; Sukoharsono, Eko Ganis; Setyarini, Any; Subekti, Imam (Economics and Business Solutions Journal, 2024)
It seems that Indonesia still lacks understanding about the disclosure of sustainability. Furthermore, it is believed that socioeconomic, cultural, governance and environmental challenges are crucial to the success of a business. The influence of corporate governance and organizational culture on sustainability performance, with strategic posture acting as a moderating variable, leads to intriguing issues that warrant further analysis. This study's population consists of all companies listed on the Indonesia Stock Exchange. Purposive sampling is used as a technique in this study. The company's website, which includes information from 2009 to 2018, was sourced from www.idx.co.id and other pertinent sources. Data collection was done, and Warp PLS algorithms were employed for the analysis method. After analyzing and debating the data, the following conclusion was reached: corporate governance and organizational culture greatly impact sustainable performance. When examining the impact of corporate governance and organizational culture on sustainability performance, strategic posture may act as a moderating factor